Correlation of efficacy of cerebro placental ratio with adverse perinatal outcome in clinically suspected IUGR pregnancies - Singh, Geeta; Gupta, Neerja; Singhal, Sangeeta; Sharma, Pramod Kishor (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: IUGR is a most common and complex problem in modern obstetrics. Most commonly use methods to assess fetal condition are BPP and NST which are not sensitive for predicting better perinatal outcome. Present study was an effort to evaluate the role of ratio of pulsatility index (PI) of middle cerebral artery and umbilical artery which is called cerebro placental ratio as the most sensitive, specific and accurate predictor of adverse perinatal outcome in clinically suspected IUGR Pregnancies. Methods: 50 clinically suspected IUGR Pregnancies attending antenatal clinics Muzaffarnagar Medical College and Hospital, Muzaffarnagar were subjected to Doppler ultrasound evaluation Doppler velocity wave form of umbilical artery and fetal middle cerebral artery were obtained. Pulsatility index ratio of MCA and umbilical artery (cerebro placental ratio) was evaluated in each case. Abnormal ratio is defined as CPR<1.08 considered as cut of value. Ratio was coo related clinically with perinatal outcome. Results: Out of 50 antenatal cases, 63% neonates had birth weight <2.5 kg. There were 6 IUD’S and 44 live births, 9 neonates were admitted to NICU, 7 neonates had 5 min. APGAR score <7 and 13 neonates were born by emergency CS. Of the 6 IUDS, 4 cases had reversal of blood flow umbilical artery and 2 cases had absent diastolic flow. In all cases of reversal Diastolic flow, IUD occurred within 7 days of diagnosis. Conclusions: CPR is the most sensitive, specific and accurate parameter in prediction of adverse perinatal outcome and thus can help in decreasing perinatal mortality.